CRYPTOCURRENCY ANALYSIS OF INDONESIAN MARKET EDUCATION FACILITIES - Maria Widyastuti; Y. Budi Hermanto (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The Indonesian market cannot be separated from the elements of information technology. The development of information technology will be closely related to the investment sector, especially finance. Cryptocurrency or digital currency is the result of the development of financial technology. Digital currencies are starting to be widely used as a means of payment via the internet. This currency was created with the aim of making payments easier and safer. The use of Blockchain technology causes transaction costs to be cheaper. Government policy through Bank Indonesia prohibits transactions using Cryptocurrency because it has a negative impact on the financial system, monetary stability and payment system in Indonesia. This research provides an understanding of Cryptocurrency to the Indonesian market. In the technology offered, cryptocurrency is a development of financial technology that allows it to replace banknotes in future financial transactions. In the future, the hope is that the government will study cryptocurrency technology more deeply so that the policies issued do not prohibit and at the same time protect the Indonesian market. Keyword : Cryptocurrency, Indonesian Market, Education Facilities